Analytical method for evaluating offensive teams` performance based on sequences of actions in basketball - Santana, F.; Lamas, L.; Ugrinowitsch, C. (Proceedings of the 2016 International Association of Computer Science in Sport (IACSS) Conference, 2016)
In invasion team sports, strategy can be inferred through the analysis of recurrent tactical patterns performed during the game. In basketball, offensive actions are connected during a ball possession producing distinct sequences, with particular features that may directly affect the offense outcome. These sequences of actions can be assessed to characterize a team strategy and its efficiency. The present study aimed to develop a method to evaluate sequences of offensive actions in basketball. Reliability and objectivity of the criteria applied for defining the different sequences of actions indicated adequate consistency (Kappa test > 0.78). Results evidenced that the proposed method was able to discriminate teams based on the registered differences of their strategy features.